К 125-летию Иовеля Григорьевича Кутателадзе (1887–1963) - Бекало, М.С.; Васильев, К.К.; Кресюн, В.И.; Годован, В.В. (Досягнення біології та медицини, 2011)
Статья посвящена жизни и деятельности И. Г. Кутателадзе — основателя высшего фармацевтического образования и научной фармации в Грузии, выдающегося фармакохимика, основателя и директора Тбилисского научно-исследовательского института фармакохимии, который с 1964 г. носит его имя, председателя научного общества фармацевтов Грузии и академика АН Грузинской
ССР. Впервые подробно исследуется одесский период его
деятельности. The article is devoted to life and activity of I. G. Kutateladze, founder of higher pharmaceutical education and scientific pharmacy in Georgia, prominent pharmacochemist,
founder and director of the Tbilisi Research Institute of Pharmacochemistry, which has had his name since 1964, chairman of scientific society of pharmacists of Georgia and
academician of AS of Georgian SSR. The Odessa period of
his activity has been studied in details for the first time.